Adipose inflammation: cause or consequence of obesity-related insulin resistance - Haiyan Xu (Dove Medical Press, 2008)
Ping Jiao, Haiyan XuHallett Center for Diabetes and Endocrinology, Brown Medical School, Providence, RI, USAAbstract: Obesity constitutes a critical risk factor for the development of many life threatening diseases, particularly insulin resistance and type 2 diabetes. Adipose tissue plays an important role in regulating whole body energy homeostatsis and obesity-related insulin resistance. Inflammation has been commonly linked to insulin resistance. Recent studies demonstrated that adipose tissue is an important source for producing inflammatory molecules in the obese state, primarily due to accumulation of macrophages. Animal models deficient in key inflammatory molecules or with reduced adipose macrophage infiltration are protected from development of obesity-related insulin resistance. Repression of adipose inflammation may be a useful approach to ameliorate obesity-associated metabolic disorders.Keywords: adipose inflammation, insulin resistance, obesity